Debt Maturity and the Effects of Growth Opportunities and Liquidity Risk on Leverage: Evidence from Chinese Listed Companies - Vijayakumaran, S.; Vijayakumaran, R. (Journal of Asian Finance, Economics and Business, 2019)
The study examines the effects of growth opportunities, debt maturity and liquidity risk on leverage, making use of a large panel of Chinese listed firms. Research on capital structure has broadened its scope from a single capital structure decision (the debt/equity choice) to various attributes of the debt in firms’ capital structure. We use the system Generalized Method of Moments estimator to control for unobserved heterogeneity and the potential endogeneity of regressors. We find a negative relationship between growth opportunities and leverage. Further, we find that while the proportion of short-term debt attenuates the negative effect of growth opportunities on leverage, it negatively affects leverage as predicted by the liquidity risk hypothesis. When we distinguish between state owned firms and private controlled firms, we find evidence that these effects are only relevant to private controlled firms. However, our analysis indicates that the economic implication of liquidity risk effect is much lower for Chinese firms than that observed in the literature for US firms. Our study suggests that these differences can be explained by differences in the institutional environment in which firms operate. This finding related to Diamond’s (1991) liquidity risk hypothesis extends our understanding of the relationship between liquidity risk and the debt maturity choice.
Keywords: Capital structure; debt maturity; liquidity risk; agency problem